ANALISIS PENGARUH HARGA, PROMOSI, KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DEARDONUTS PADA PLATFORM E-COMMERCE: analysis of the influence of promotions, prices, consumer confidence on purchasing decisions of dear donuts on e-commerce platforms - Evangelino, Ishack Bezhaliel Rockhy (PERFORMA, 2022)
Dear Donut’s is a business that operates in the F&B, with a pastry base, namely by producing Donuts which was established in 2019. The purpose of this study was to determine the effect of promotion on purchasing decisions, to determine the effect of price on purchasing decisions, to determine the effect of consumer trust on purchasing decisions. This research uses quantitive methods. The subject used in this research are 100 respondents who are consumers of Dear Donut’s. the collection of the required data is done through filling out a survey question that have been presented into a google form which will later be filled out by cunsumers from Dear Donut’s. Data processing is done usi SPSS software. The result of data processing show that promotion and consumen trust have a significant and significat effect on purchasing decisions, for price vane no significant effect on purchasing decisions